PRINSIP POLLUTER PAYS PADA PENCEMARAN LAUT AKIBAT TUMPAHAN MINYAK: HUKUM LINGKUNGAN INTERNASIONAL - Muhammad Ivandri; Arlina Permanasari (Reformasi Hukum Trisakti, 2023)
When enforcing environmental laws, both preventive and punitive measures, the polluter pays approach is particularly beneficial. The problem is how the Polluter Pays principle is carried out by countries affected by oil spills in their territorial sea and whether the Polluter Pays principle is carried out by countries affected by sea pollution. This study discusses the implementation of the Polluter Pays principle due to marine pollution due to oil spills and the imposition of compensation. Normative research with literature reviews based on court records and facts that arise in cases of tanker accidents and oil rig leaks is used, data use descriptive analysis. The data sources used are primary and secondary legal materials. The results of the research and discussion illustrate the application of the Polluter Pays principle in cases that result in marine pollution by oil. Polluters also carry out compensation for affected countries by using prices prevailing in the market, taking certain actions and implementing restoration of environmental functions. It was concluded that the application of the Polluter Pays principle is quite effective in dealing with pollution at sea, so that the application of the Polluter Pays principle needs to be fully enforced in marine environmental disputes.